The Effectiveness of Mealworms (Tenebrio molitor) as an Alternative Feed to Increase Quail Egg Productivity and Quality - Husna, Asmaul; Haryadi; Wahyudi (Faculty of Animal Science, Universitas Brawijaya, 2025)
Alternative feed is important to consider so that feed production costs can be reduced and income can be increased. Mealworms are a source of animal protein with high nutritional value and a complete amino acid profile, making them an alternative feed source worth considering. However, the incorporation of mealworms into quail diets, particularly in Indonesia, has not been extensively studied, creating a gap that this research aims to address. The purpose of this research was to use mealworms (Tenebrio molitor) as an alternative feed to improve the productivity and egg quality of quail. This research used a completely randomized design (CRD) with 5 treatments and 4 replications. In treatment A, 0% MF was added to the rations; in treatment B, 5% MF was added to the rations; in treatment C, 10% MF was added to the rations; in treatment D, 15% MF was added to the rations; and in treatment E, 20% MF was added to the rations. The parameters observed were the productivity of laying quail (feed consumption, egg weight, egg production, and feed conversion) and the quality of quail eggs (crude protein, crude fat, yolk color, and quail eggshell weight). The results revealed that the addition of mealworm flour to the laying quail rations significantly affected (P<0.05) the feed consumption, egg weight, egg production percentage, and feed conversion of laying quail but did not significantly affect (P>0.05) egg crude protein content, egg crude fat content, yolk color, or eggshell weight. In conclusion, the addition of up to 15% mealworm flour to the laying quail feed mixture did not have a negative effect on quail performance or egg quality, indicating its potential as a sustainable alternative protein source.